Influence of main parameters on the displacement process by spontaneous imbibition based on LBM - Tianju Wang; Hongsheng Guo; Li Lu; Xuhui Zhang; Yan Zhang; Zhiwei Hao; Xiaobing Lu (PLoS ONE, 2025)
The imbibition of water into the pores of tight oil/gas reservoir can displace the oil/gas out. Thus it is an important method to improve the recovery efficiency of tight shale gas and oil. This paper investigated the influence of four main dimensionless parameters on the spontaneous imbibition based on a pores distribution of a real shale sample. The results show that the connectivity has the greatest impact on the average imbibition velocity while the impact of the contact angle is the smallest. The capillary number has the greatest impact on the oil displacement efficiency. The impact of main factors on imbibition and displacement is not monotonic, but rather a combination of these factors.